Portugal - Estanqueiro, Ana (2013)
Portugal has few indigenous energy resources, such as those that satisfy the majority of the energy needs of the economically developed countries, such as oil, gas, and coal. This situation leads to a large dependence on foreign economies for fossil primary resources. In this context, the contribution of renewable energies and the need to improve their penetration becomes of strategic relevance for the country’s development. In 2006, the total renewable sources installed capacity was 6,961 MW. The total electric energy production from renewables has shown an impressive 86% growth rate with respect to the end of 2005, its final value being reported as 16,120 GWh. This growth was strongly correlated with the variation in hydropower production, about 124%. In what concerns to wind energy, as will be shown in the next paragraphs, there was a moderate growth in the installed capacity when compared to previous years. In 2006, the 2005 policy continuance was verified, with special relevance to the ending of the first phase of the 1,500 MW public call for wind park grid connection opened in July 2005.